Study of antarctic lichens as environmental biomonitors in the Admiralty Bay: Preliminary study of trace elements contents by neutron activation analysis - Gonzáles, Susana (2002)
Al, As, Cu, Fe, Mn and Ti contents were analyzed for the epilithic antarctic lichen Usnea antarctica, used as a biomonitor for air quality. The samples were taken in the surrounding area of the Peruvian scientific station "Machu Picchu" on King George Island, in the Southern Shetland Archipielago (Antarctica). These elements have been assayed by Neutron Activation Analysis (NAA). The preliminary obtained results support the hypothesis that an atmospheric circulation of chemicals exists on the assessed area and the activities developed at the different scientific stations located on this island would be a potential source of chemical pollutants for the evaluated area.